2018
DOI: 10.1101/358812
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A computational protocol to characterize elusive Candidate Phyla Radiation bacteria in oral environments using metagenomic data

Abstract: 24Several studies have documented the diversity and potential pathogenic associations of 25 organisms in the human oral cavity. Although much progress has been made in 26 understanding the complex bacterial community inhabiting the human oral cavity, our 27 understanding of some microorganisms is less resolved due to a variety of reasons. One 28 such little-understood group is the candidate phyla radiation (CPR), which is a recently 29 identified, but highly abundant group of ultrasmall bacteria with red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…This hitherto undiscovered CPR group of organisms showcases a remarkable diversity, encompassing over 35 distinct phyla, inhabiting a wide range of ecological niches. They also lack the genes responsible for encoding a CRISPR/Cas bacteriophage defense system [ 45 , 46 ].…”
Section: Evolution: Microorganism To Microbiomementioning
confidence: 99%
See 2 more Smart Citations
“…This hitherto undiscovered CPR group of organisms showcases a remarkable diversity, encompassing over 35 distinct phyla, inhabiting a wide range of ecological niches. They also lack the genes responsible for encoding a CRISPR/Cas bacteriophage defense system [ 45 , 46 ].…”
Section: Evolution: Microorganism To Microbiomementioning
confidence: 99%
“…This is achieved through their ability to control the structural arrangement and operational behavior of the oral microbiome. These factors have been shown to have correlations with oral diseases, such as periodontitis and halitosis [ 45 , 46 , 57 ].…”
Section: Evolution: Microorganism To Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…Two years after a CPR sequence was first detected, in 1998, the 16S rRNA phylogenetic tree revealed CPR sequences as a distinct phylum independent of archaea and eukaryotes but related to bacteria ( Figure 1 ) [ 31 ]. Due to significant divergent genetic sequences, some studies have shown the inadequacy of using 16S rRNA for CPR classification [ 7 , 32 ]. However, the use of other conserved coding genes, such as ribonucleotide reductase (RNR), topoisomerase IIA (Topo IIA), elongation factor 1 (EF1), DNA-dependent RNA polymerase subunit II (RNAP II), thymidylate synthase (ThyA), and DNA polymerase, has ultimately resulted in a very similar classification of CPR genomes [ 32 , 33 ].…”
Section: Cpr Genomes: Discovery Of a New Division Is Challenging For ...mentioning
confidence: 99%
“…Due to significant divergent genetic sequences, some studies have shown the inadequacy of using 16S rRNA for CPR classification [ 7 , 32 ]. However, the use of other conserved coding genes, such as ribonucleotide reductase (RNR), topoisomerase IIA (Topo IIA), elongation factor 1 (EF1), DNA-dependent RNA polymerase subunit II (RNAP II), thymidylate synthase (ThyA), and DNA polymerase, has ultimately resulted in a very similar classification of CPR genomes [ 32 , 33 ]. Thus, a recent genomic analysis conducted by Megrian et al showed the conserved presence of division and cell wall (dcw) genes with the necessary order (synteny) in over 1000 bacterial genomes, including CPRs [ 34 ].…”
Section: Cpr Genomes: Discovery Of a New Division Is Challenging For ...mentioning
confidence: 99%